URBAN PLANNING FACTORS OF LAND USE MONITORING OF UNITED TERRITORIAL COMMUNITIES - Kanivets, O.; Goi, V. (Municipal economy of cities. Series: «Economy science», 2024)
There is proof that in the conditions of ensuring transformational processes, issues of formation and use of land and increasing the efficiency of their use at the local level arise. In addition, the presented processes deepen because of the reform of local self-government, which ensures the effectiveness and interaction of stakeholders. The core element in developing these relationships is the united territorial communities and land use directions and features, with consideration of the influence of factors. In the system of land relations of united territorial communities, urban planning factors that influence the development and implementation of modern monitoring tools are particularly important. The study aims to determine the urban planning factors of land use monitoring of united territorial communities. To achieve the goal, we solved the following tasks: characterisation of urban planning factors of land use monitoring and highlighting the peculiarities of the formation of urban planning factors of land use of united territorial communities. Among the peculiarities of the development of land use monitoring of united territorial communities is also the identification of a system of urban planning factors, namely the levels: development and implementation of land management projects regarding the arrangement of territories for urban planning needs; formation and application of the urban development support system; development and implementation of monitoring procedures of urban planning activities; formation and use of urban cadastre; provision of architectural and construction control; development and implementation of comprehensive plans; change in the level of construction activity in united territorial communities. We have formed local factors of urban planning support for land use monitoring of united territorial communities, with most of them determined by qualitative methods. Estimating the indicator of the change in the level of construction activity in the united territorial communities uses quantitative methods. It creates a basis for implementing monitoring procedures through the application of urban planning provision of land use of united territorial communities.